Dipping Seedling’s Rice Root with Indigenous Microorganisms from Mimosa invisa to Control Blast Disease and Increased Rice Production in Purwoasri Village, Jember - Abd. Rouf Rizqon; Wiwiek Sri Wahyuni (Universitas Gadjah Mada, 2021)
Rice blast disease has become endemic in Purwoasri Village, Gumukmas District, Jember Regency since 2018; this was due to the use of the Ciherang variety planted continuously. The study aimed to use the indigenous microorganisms IM) suspension made by farmers from Pos Pelayanan Agens Hayati (PPAH, Biological Agent Service Post) in Ambulu District as the control agent for blast pathogens and increased rice production. The roots of rice seeds were dipped in IM suspension at a concentration of 50 mL/L for 2 hours to penetrate to roots. Seedlings with IM were planted in a block of 250 m2, and control was also planted in the same block size. In the IM-treated block, the incidence and severity of blast disease decreased compared to the control. The root treated by IM dipping was also increased the plant growth, including root architecture, root length, root volume, and the number of tillers/plant; furthermore, it improved rice production. It was found that IM suspension contained pseudomonad fluorescent and Bacillus sp. that belong to Plant Growth Promoting Rhizobacteria (PGPR) group.